ECE678: Special Topics in Computer Graphics and Animation / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2014)
This course will study a selected advanced topic and techniques of current interest in computer graphics and animation. Teaching and learning will focus on new concepts not included in the existing course syllabus and includes recent development and progress in the subject area.